Dignity Therapy Training for the Healthcare Professionals: Lessons Learned From an Italian Experience - Buonaccorso, Loredana; Alquati, Sara; Ghirotto, Luca; Annini, Alice; Tanzi, Silvia (Frontiers in Psychology, 2022)
Introduction Dignity therapy (DT) is brief psychotherapy targeting psychological and existential suffering among patients with a life-limiting illness. Studies have been conducted on the use of DT by healthcare professionals. In Italy, the current legislation defines that any form of psychotherapy may be performed exclusively by psychotherapists. Consequently, this intervention is unlikely to be used by other healthcare professionals. Herein, we will describe a training on DT not as a psychotherapy intervention but as a narrative intervention for non-psychotherapists health care professionals. Finally, we will explore the potential enablers/barriers as experienced by palliative care physicians and nurses. Methods The study was conducted in the Psycho-Oncology Unit within the Cancer Research Hospital of Reggio Emilia (Italy). It consisted of an exploratory qualitative case study. Data were collected employing observations and interview data and thematically analyzed. Results The training was attended by six physicians and ten nurses and took place during two-afternoon sessions for 10 h. Two participants put their training into practice and administered DT under the supervision of a psychotherapist. Data analysis highlighted five overarching themes relating to the training experience and direct use of DT, namely, (i) time required, (ii) psychological skills, (iii) patient’s disease awareness, (iv) patient’s life history, and (v) distinguishing DT from Advance Care Planning. Conclusion Palliative care professionals found DT to be a valuable non-pharmacological hospital-based intervention to address the person beyond the patient and his clinical conditions. In our experience, considering that in Italy, psychotherapy is an intervention that psychotherapists can only perform, it can help organize different training on DT for psychotherapists and other healthcare professionals.